Exponential stabilization of nonlinear systems under saturated control involving impulse correction. (May 2023) - Yu, Miaomiao; Wu, Shuchen; Li, Xiaodi
Abstract: This paper studies the problem of locally exponential stabilization ( LES ) of nonlinear systems under a class of hybrid control in the framework of actuator saturation, where the limitation of actuator saturation on both continuous state feedback control and impulsive control are fully considered. Based on impulsive control theory and differential inclusion approach, some sufficient conditions for LES are derived, where a novel set inclusion relation is proposed to handle the double saturation nonlinearities. Different from the existing results that each part of saturated hybrid control ( SHC ) is required to stabilize the system individually, our results relax the requirement by making full use of the correction effect of the impulse. Moreover, the maximum of estimation of domain of attraction is obtained by a convex optimal problem and corresponding algorithm. The result is applied to the robustness for a class of nonlinear systems. Finally, the validity of the results is shown by two examples and their simulations, where the synchronization problem of Chua's oscillator is illustrated in the framework of actuator saturation.